Procedural adverse events in pediatric patients with sickle cell disease undergoing chronic automated red cell exchange. Issue 3 (24th January 2022) - Wade, Jenna; Yee, Marianne E. M.; Easley, Kirk A.; Pahz, Shannon; Butler, Hailly; Zerra, Patricia E.; Josephson, Cassandra D.; Fasano, Ross M.
Abstract: Background: Chronic automated red cell exchange (RCE) is increasingly employed for sickle cell disease (SCD). There is a paucity of data on the incidence of RCE adverse events (AEs) and potential patient and procedural risk factors for AEs. Methods: A retrospective review of pediatric SCD patients receiving chronic RCE over 3 years was performed to determine the frequency of AEs and identify procedural and patient AE risk factors. AE incidence, AE rate, incidence rate ratios (IRRs), and relative risks (RRs) were calculated based on various procedural and patient characteristics by univariable (UV) and multivariable (MV) analyses. Results: In 38 patients receiving 760 procedures, there were 150 (19.7%) AEs, 36 (4.7%) were symptomatic AEs. AE rates were 20.2 [95% CI 17.2, 23.6] and 4.8 [95% CI 3.49, 6.70] per 100 person months for AEs and symptomatic AEs, respectively. AE incidences were: hypocalcemia (117; 15.4%), dizziness (22; 3.0%), hypotension (15; 2.0%), and nausea (14; 1.8%). Patients with baseline Hct ≥30% experienced more total AEs and symptomatic AEs. Patients with pre‐procedure systolic BP <50th percentile, severe CNS vasculopathy, and non‐SCA genotype (HbSC or Sβ + thalassemia) exhibited more total AEs. IHD depletion was not associated with an increased incidence of AEs or symptomatic AEs. Conclusion: SCD patients with Hct ≥30%, systolic BP <50th percentile, severe CNS vasculopathy, and possibly non‐SCA genotype may be at higher risk for RCE‐related AEs. The effect of IHD on AE risk is likely minimal. Individualized AE risk assessment should be performed in all SCD patients undergoing chronic automated RCE.